Pengaruh Lingkungan Kerja dan Rotasi terhadap Kinerja Pegawai pada Sekretariat BPSDM Perhubungan Kementeria Perhubungan (Jurnal Manajemen Kreatif dan Inovasi, 2025)
This study aims to determine the effect of work environment and rotation on employee performance at the Secretariat of the Human Resources Development Agency (BPSDM) of the Ministry of Transportation. A conducive work environment and the implementation of proper job rotation are believed to be able to increase employee motivation and work productivity. This study uses a quantitative approach with a survey method by distributing questionnaires to 30 respondents who are employees of the BPSDM Secretariat. Data analysis was carried out using multiple linear regression to test the simultaneous and partial effects between independent variables and dependent variables. The results of the study indicate that both the work environment and rotation have a positive and significant effect on employee performance, both partially and simultaneously. This indicates that improving the quality of the work environment and implementing proper job rotation can contribute to improving employee performance. Data collection used in this study was a questionnaire whose results were calculated using SPSS Version 25. The results of the F test in this study, the calculated F value obtained was 173.617 which means> F table 3.35 where the significance level is <0.05, which is 0.000. Therefore, the hypothesis that simultaneously states that the Work Environment and Rotation have a significant effect on employee performance is accepted.